Assistance in using the marketplace platform for scavenger groups - Lucia Ari Diyani; Kristiana Widiawati; Indra Muis (University of Merdeka Malang, 2022)
A problem in small-scale industries is the lack of marketing knowledge of digital technology. Based on this problem, this Community Service activity was carried out with the aim of increasing the knowledge of the scavenger group who are members of the Tunas Mulia Foundation, in the Bantar Gebang Integrated Waste Management Site, Bekasi. Activities are carried out through training and assistance in using sales applications through the marketplace platform. The purpose of this activity is to help increase the income of scavenger families by expanding the market through digital technology. The method used is the presentation of the material at the location of the Foundation. The material is given by the lecturer and then direct practice in making the platform is assisted by students as a companion to the participants. A total of 40 scavengers who participated in the mentoring were divided into two classes. The PKM activity was carried out for half a month, starting on December 14-30, 2021. The results of this activity were very satisfying for the participants, as seen from the results of the questionnaire and had increased the ability of participants to market their products through the marketplace and proved to significantly increase family income.